Penyelenggaraan Pos Upaya Kesehatan Kerja Terintegrasi di Desa Wisata Kasongan, Bantul- D.I. Yogyakarta - Agustin, Helfi; Arianto, Machfudz Eko; Rifai, Muchamad (Jurnal Kesehatan Komunitas, 2023)
Two hundred and twenty-two public health centers have organized Basic Occupational Health and Safety (BOHS) in Yogyakarta province in 2022. Based on previous research, most of the implementation of the BOHS of community health centers is not yet running and specific. One of the BOHS for tourism sector workers is the “Kasongan Sehat”, in the Kasongan Tourism Village. This qualitative research aims to analyze the implementation of the BOHS in the “Kasongan Sehat”. The research subjects were occupational health trainers at the Community Health Center level, cadres, pottery industry workers in Kasongan, and hamlets selected using purposive sampling. In-depth interview and observation data collection techniques. The analysis uses the content analysis method. Research findings; The basis for administering the BOHS is Bantul Regent's regulation number 42 of 2015. This post has implemented an integrated BOHS by Minister of Health Regulation number 100 of 2015, which can be seen from the combination of their activities and management. Activities have been running regularly; including measuring blood pressure, body weight, first aid, and providing referrals to community health centers. The Community Health Center has distributed facilities and infrastructure and held first aid training for treating wounds for cadres. In general, occupational health service activities by cadres at the “Kasongan Sehat” have not been implemented comprehensively, due to a lack of training on OHS and the BOHS has just been revitalized after being stagnant after the 2006 Yogya earthquake. Specific training and guidance on BOHS are needed for supervisors as well as cadres.